MEDAN MAKNA ALAT RUMAH TANGGA YANG TERBUAT DARI KAYU PADA MASYARAKAT KAILI - Muh. Asri B. (Multilingual, 2015)
This paper is about the description of meaning field of housewares made from woods in Kaili society. The method used in this research was descriptive with recording and interviewing method. The analysis was processing by grouping, classifying the similar and dissimilar data and classifying the similar but different data into another group. The data were analyzed into 34 houseware’s vocabularies based on the material and function. Based on the material, there are clay and stone houseware. Based on the function, it can be use as(1) grilling, (2)cleaving, (3) saving, (4) grilling, (5)seat (6)storage, (7) pricking, (8) place mat, (9), collecting, (10)chopping, (11) sleeping place, seat. (12)swabbing , (13) cleaning, (14) sucking, (15) grinding, milling, (16)digging, (17) grindding, collecting, (18) stirring, scooping (19) illuminating (20)drawing water